Bilateral tax competition and regional spillovers in tax treaty formation - Petkova, Kunka,Stasio, Andrzej,Zagler, Martin (European Commission, 2020)
Tax treaties are often seen as a means to mitigate fierce tax competition. We challenge this view by arguing that taxes on passive income reduce e↵ective average tax rates, and induce neighbouring countries to react by reducing bilateral tax rates. As opposed to traditional tax competition, where every foreign investor would benefit from lower tax rates, we show that countries also engage in cutting tax rates for investors from a particular country, leaving taxes for everyone else una↵ected. We call this bilateral tax competition, and we test these predictions empirically. We focus on the four treaty withholding tax rates on passive income - portfolio dividends, participation dividends, interest, and royalties - and collect these rates for 3,000 tax treaties and amending protocols signed between 1930 and 2012. We find a positive relationship in the negotiated withholding tax rates of a destination country's tax treaty and destination country competitors' past tax treaties with the same source country. This relationship is strongest for the tax rates on interest and royalties, and varies from an average elasticity between 0.19 and 0.36 with both source and destination country being an OECD member, and an average elasticity up to 0.64 when both countries are tax havens.
10419/248820
Keywords: Graue Literatur; tax competition; international taxation; double taxation treaties; taxtreaty formation